Menggereja dalam Dunia Metaverse - Evita Putri Sibarani; Fernando Dapot Hamonangan L. Tobing (STT HKBP Pematangsiantar, 2024)
In recent years, Augmented Reality (AR) technology has been in the spotlight, especially after Mark Zuckerberg, CEO of Facebook, changed the name of Facebook to Meta. Metaverse, which is a simulation of the real world on the internet, marks a new evolution in virtual interaction. The superiority of the metaverse in facilitating communication and other activities has changed social dynamics, including in religious contexts such as evangelism. From the beginning of scriptural media printing to the time of the pandemic, reliance on the metaverse as a medium of interaction and connection has increased. This change was triggered by various crises faced during the period. This research aims to shed light on the evolving relationship between the church and the metaverse, focusing on the changes in the religious mediation process that transformed the dynamics of mission from linear and hierarchical to more flexible and heterarchical. Although mediation is often perceived as a simplification, it can be a source of enriching ideas.